Peran Pemerintah, Sektor Swasta Dan Modal Sosial Terhadap Pembangunan Pariwisata Berkelanjutan Berbasis Masyarakat di Kota Kupang Nusa Tenggara Timur - Ringa, Maria Bernadetha (P3M- Politeknik Negeri Kupang, 2018)
The purpose of this study was to find out (1) Influence of the role,of the government, the role of the private sector and social capital on community participation in the city of Kupang. (2) Influence of the role,of government, private sector and social capital and community participation in sustainable tourism development in the city of Kupang. (3) The role of community participation, in meditating on the role of government variables, the role of the private sector, social capital, on sustainable tourism development. (4) To design the right strategy in the development of sustainable tourism in the city of Kupang. This research was carried out in the city of Kupang, East Nusa Tenggara Province, in six subdistricts which have tourism, marine tourism, religious tourism, and artificial tourism. The sample in this study was 270 respondents. Data collected by questionnaires were then analyzed using SEM-PLS, and to strengthen tourism strategies in Kupang city, SWOT analysis was used. The results of the research and data analysis show that : (1) The role of government, the role of the private sector, and social capital directly have a positive and significant effect on public participation. (2) The role of the private sector does not have a significant effect on sustainable tourism development. (3) Community participation was able to play a part in mediating partially the role of the government, the role of the private sector and social capital towards sustainable tourism development in the city of Kupang in East Nusa Tenggara.